A proporção de plasma rico em plaquetas/enxerto ósseo autógeno pode influenciar o reparo ósseo de defeito de tamanho crítico: estudo radiográfico em calvária de ratos - Nagata, Maria José Hitomi [UNESP]; Messora, Michel Reis; Campos, Natalia de [UNESP]; Pola, Natalia Marcumini [UNESP]; Salzedas, Leda Maria Pescinini [UNESP]; Bomfim, Suely Regina Mogami [UNESP]; Faleiros, Paula Lazilha [UNESP]; Santinoni, Carolina dos Santos [UNESP]; Bosco, Álvaro Francisco [UNESP]; Garcia, Valdir Gouveia [UNESP] (My University, 2011)
Introduction: It has been suggested that bone grafts combined with platelet rich plasma (PRP) present greater density than bone grafts without PRP after healing process. However, this result may depend on proportion PRP/autogenous bone (AB) graft used. Objective: The purpose of this study was to analyze radiographically the influence of the proportion PRP/particulate autogenous bone (AB) graft on bone healing in surgically created criticalsize defects (CSD) in rat calvaria. Material and method: 50 rats were divided into 5 groups: C, AB, AB/PRP-50, AB/PRP-100 and AB/PRP-150. A 5 mm diameter CSD was created in the calvarium of each animal. In Group C the defect was filled by blood clot only. In Group AB the defect was filled with 0.01 mL of AB graft. In groups AB/ RP-50, AB/PRP-100 and AB/PRP-150 the defects were filled with 0.01 mL of AB graft combined with 50, 100 and 150 µL of PRP, respectively. All animals were euthanized at 30 days post-operative. Standardized radiographic images of the rat calvaria were obtained using Digora System (Soredex, Finland). The images were evaluated by three examiners using scores that indicated the percentage of radiopacity of the defect. The obtained data were subjected to statistical analysis (Kruskal-Wallis test, p < 0.05). Result: Group C presented radiopacity significantly lower than groups AB, AB/PRP-50, AB/PRP-100 and AB/PRP-150. Group AB/PRP-50 showed radiopacity significantly greater than groups AB/PRP-100 and AB. Conclusion: It can be concluded that the proportion PRP/AB graft influences bone healing in CSD in rat calvaria.

Introdução: Tem sido sugerido que enxertos ósseos associados ao Plasma Rico em Plaquetas (PRP) cicatrizam com maior densidade que os enxertos sem PRP. Contudo, esse resultado parece depender da proporção PRP/enxerto ósseo utilizada. Objetivo: O propósito deste estudo foi avaliar, radiograficamente, a influência da proporção PRP/enxerto de Osso Autógeno (OA) no reparo ósseo de defeitos de tamanho crítico (DTCs) criados cirurgicamente em calvárias de ratos. Material e método: Cinquenta ratos foram divididos em cinco grupos: C, OA, OA/PRP-50, OA/PRP-100 e OA/PRP-150. Um DTC de 5  mm de diâmetro foi criado na calvária de cada animal. No Grupo C, o defeito cirúrgico foi preenchido somente com coágulo sanguíneo. No Grupo OA, o defeito foi preenchido com enxerto de OA particulado. Nos grupos OA/PRP-50, OA/PRP-100 e OA/PRP-150, o defeito foi preenchido com enxerto de OA particulado associado a 50, 100 ou 150 µL de PRP, respectivamente. Os animais foram eutanasiados aos 30 dias pós-operatórios. Imagens radiográficas padronizadas das calvárias foram obtidas com o sistema Digora (Soredex, Finlândia). As imagens foram avaliadas por três examinadores por meio de escores, que indicaram o percentual de radiopacidade dos defeitos. Os escores obtidos foram submetidos ao Teste de Kruskal-Wallis (p < 0,05). Resultado: O Grupo C apresentou radiopacidade significativamente menor que os grupos OA, OA/PRP-50, OA/PRP-100 e OA/PRP-150 (p < 0,05). O Grupo OA/PRP-50 apresentou radiopacidade significativamente maior que os grupos OA/PRP-100 e OA (p  <  0,05). Conclusão: Dentro dos limites deste estudo, pode-se concluir que a proporção PRP/enxerto de OA influencia a cicatrização de DTCs criados em calvárias de ratos.
The proportion platelet-rich plasma/particulate autogenous bone graft may influencebone healing in critical-size defects: a radiographic study in rat calvaria
Keywords: Bone regeneration; Growth factors; Platelets; Radiography; Regeneração óssea; Fator de crescimento; Plaquetas; Radiografia